2011
DOI: 10.1063/1.3592254
|View full text |Cite
|
Sign up to set email alerts
|

Stability of Ag nanocrystals synthesized by ultra-low energy ion implantation in SiO2 matrices

Abstract: Ultra low energy ion implantation is a promising technique for the wafer-scale fabrication of Silver nanoparticle planar arrays embedded in thermal silica on silicon substrate. The stability versus time of these nanoparticles is studied at ambient conditions on a time scale of months. The plasmonic signature of Ag NPs vanishes several months after implantation for as-implanted samples, while samples annealed at intermediate temperature under N2 remain stable. XPS and HREM analysis evidence the presence of Silv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
29
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 32 publications
3
29
0
Order By: Relevance
“…In particular, we have shown that a post-implantation annealing process strongly limits silver oxidation, which otherwise excludes the use of Ag NCs on free surfaces. 12 The optical properties of our layers have been examined both experimentally and theoretically in Refs. 10, 11, and 13. In this paper, we focus our attention on material science issues, with the objective to give a better understanding of a)…”
Section: Introductionmentioning
confidence: 99%
“…In particular, we have shown that a post-implantation annealing process strongly limits silver oxidation, which otherwise excludes the use of Ag NCs on free surfaces. 12 The optical properties of our layers have been examined both experimentally and theoretically in Refs. 10, 11, and 13. In this paper, we focus our attention on material science issues, with the objective to give a better understanding of a)…”
Section: Introductionmentioning
confidence: 99%
“…7 The modification of the optical properties by LSP coupling depends on the EC rates and it is related to the LSP energy and spacer thickness between the metal nanostructure and the active layer. 13,14 These considerations make it important to better understand the stability and contamination issues of the metal nanostructure produced by alternative methods and to study the characteristics of LSPs associated with such alternative structures. 9,10 In previous reports the metal thin film was deposited on the surface by an e-beam evaporator and then an annealing process was performed to form the metal nanostructure.…”
Section: Introductionmentioning
confidence: 99%
“…13 In the case of Ag, embedding of the NPs in a transparent dielectric matrix avoids their alteration (oxidation and sulfuration) but also their dissemination, while preserving their plasmonic properties and keeping a flat and reusable surface. 14 The LSPR frequency and intensity depend not only on the noble metal NP material, shape, and size but also on its environment, i.e., of the embedding matrix. Despite their importance, the effects caused by capping of dielectric materials (oxides or nitrides) on the structure (morphology and composition) and optical response of noble metal NPs are poorly studied.…”
mentioning
confidence: 99%